Making modernity in the Islamic Mediterranean - Graves, Margaret S.; Seggerman, Alex Dika (Indiana University Press, 2022)
"The Islamic world's artistic traditions experienced profound transformation in the 19th century as rapidly developing technologies and globalizing markets ushered in drastic changes in technique, style, and content. Despite the importance and ingenuity of these developments, the 19th century remains a gap in the history of Islamic art. To fill this opening in art historical scholarship, Making Modernity in the Islamic Mediterranean charts transformations in image-making, architecture, and craft production in the Islamic world from Fez to Istanbul. Contributors focus on the shifting methods of production, reproduction, circulation, and exchange artists faced as they worked in fields such as photography, weaving, design, metalwork, ceramics, and even transportation. Covering a range of media and a wide geographical spread, Making Modernity in the Islamic Mediterranean reveals how 19th-century artists in the Middle East and North Africa reckoned with new tools, materials, and tastes from local perspectives"--